Reporting strategies in the novel Nỗi buồn chiến tranh and its English translated version The Sorrow of War by Phan Thanh Hao and Frank Palmos: A systemic functional comparison = Các chiến lược thông báo trong tiểu thuyết “Nỗi buồn chiến tranh” và trong bản dịch “The Sorrow of War” của Phan Thanh Hảo và Frank Palmos: So sánh theo lý thuyết ngữ pháp chức năng hệ thống - Vũ, Thị Kim Ngân (2020)
The thesis endeavors to make a contrastive analysis of the novel Nỗi buồn chiến tranh and its translated version by Phan Thanh Hao and Frank Palmos. The theoretical framework employed for analysis and comparison of the novel and its translated version is systemic functional linguistics. The research findings show that there are some similarities and differences in using reporting strategies in the source novel and its translated version. Both two versions share the same aim to report the characters’ locutions and ideas and consist of reporting thoughts and reporting speeches. However, three main differences in applying reporting strategies are also found out: in the structure of the clauses in the complexes, in the uses of reporting verbs and in the appearance of non-linguistics conventions. By making a comprehensive and detailed study, this thesis is a meaningful application of systemic function grammar to learning and teaching translation, and translating.